Strengthening Performance of Secondary Students Along Low-Moderate-High Abilities in Physics Using Group Dynamics and Visual Cue Strategies - Achor, Emmanuel; Odoh, Comfort; Ngbea, Philip (Papanda Publisher, 2025)
This study examined how group dynamics and visual cues strategies can foster academic performance of Senior Secondary II students of different cognitive abilities in Physics in Benue State, Nigeria. Specifically, the study determined which of the ability groups (i.e low, moderate and high) gained more when group dynamics and visual cues strategies were used in teaching Physics. The study adopted quasi-experimental design of pre-test, post-test non-randomized control group type. The population for this study comprised 815 SS II students offering Physics in public secondary schools in Makurdi Local Government Area in the 2023/2024 academic session, while a sample of 114 students was selected using multi-stage sampling procedure. The instruments for data collection are Physics Performance Test (PPT) and Student Cognitive Ability Test (SCAT). The PPT SCAT were validated by three experts. The reliability coefficient of the instruments were obtained using K-R20 and found to be 0.81 for PPT and 0.72 for SCAT. The collected data were analyzed using mean and standard deviation to answer research questions and ANCOVA to test the null hypotheses at 0.05 level of significance. Findings revealed that the mean gain in academic performance score of students taught Physics using group dynamics strategy was 22.75 for high, 18.47 for moderate and 3.45 for low ability students. There was significant difference in the mean academic performance scores of low, moderate and high cognitive ability students when group dynamics strategy was used in teaching Physics.The mean gain in academic performance score of students taught Physics using visual cues strategy was 22.79 for high, 15.72 for moderate and 3.22 for low ability students. There was significant difference in the mean academic performance scores of low, moderate and high cognitive ability students when visual cues strategy was used in teaching Physics. The study has established that for both experimental groups (that is, group dynamics and visual cues strategies) the performance of the students increases in the order of low ability →moderate ability → high ability. The study concludes that the effectiveness of the two strategies is dependent on cognitive abilities of the students. The high ability students benefited most, followed by the moderate ability students while the low ability students benefited the least from each of the strategies. It was therefore recommended that teachers of Physics should employ group dynamics and visual cues teaching strategies in Physics class to ensure effective teaching and enhance academic performance of students in the subject and to ensure successful teaching and learning of the subject for improved cognitive abilities of students in Physics, among others.